2003
DOI: 10.1111/j.1365-2311.2003.00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonising aliens: caterpillars (Lepidoptera) feeding on Piper aduncum and P. umbellatum in rainforests of Papua New Guinea

Abstract: Abstract. 1. Caterpillar assemblages feeding on two alien plants, Piper aduncum and P. umbellatum, were studied in lowland rainforest in Papua New Guinea and compared with assemblages from 69 species of native woody hosts, including congeneric P. macropiper.2. Species richness of caterpillars feeding on P. aduncum (29 species per 1500 m^ of foliage) and P. umbellatum (36 species) was higher than the median richness for the 69 native hosts (23 species).3. The probability that a caterpillar species colonised ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 41 publications
(64 reference statements)
1
55
0
1
Order By: Relevance
“…In spite of the toxicity of the chemical constituents found in the leaf extracts of the two species of Piper studied, it is interesting to note that P. aduncum is the highly preferred host for a number of caterpillar species [23]. Such selectivity in the assemblages and feeding preferences of the caterpillar may suggest that the accumulation of the phytochemicals, in particular dill apiole, derived from this species could serve as a chemical defence for the caterpillars to deter excessive predation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the toxicity of the chemical constituents found in the leaf extracts of the two species of Piper studied, it is interesting to note that P. aduncum is the highly preferred host for a number of caterpillar species [23]. Such selectivity in the assemblages and feeding preferences of the caterpillar may suggest that the accumulation of the phytochemicals, in particular dill apiole, derived from this species could serve as a chemical defence for the caterpillars to deter excessive predation.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, comparative studies conducted on the feeding habits of caterpillars (Lepidoptera) on two exotic Piper species (P. aduncum and P. umbellatum) with the native host species of PNG indicated a higher preference for the two introduced species [23]. The higher assemblage and feeding preference as well as species diversity on P. aduncum is particularly interesting.…”
Section: Introductionmentioning
confidence: 99%
“…The latter possibility can be ruled out by our extensive feeding trials, although even then the possibility still persists that a confirmed trophic association occurs but exceptionally in nature. Novotny et al (2003) densiciliatum and XV, both of which we excluded from our analysis due to their small data sets. The native New Guinean P. macropiper ranked even lower than most of our species (1.684).…”
Section: Discussionmentioning
confidence: 99%
“…tact between the novel partners (Brändle et al, 2008;Karolewski et al, 2017, but see Andow & Imura, 1994 and host specifi city (Novotny et al, 2003;Roques et al, 2009;Walczak et al, 2017). The ability of an insect to successfully colonize new hosts is also strongly determined by the plant's physical, chemical, and phenological traits (Coley & Barone, 1996;Loranger et al, 2013;Bogdziewicz et al, 2018).…”
mentioning
confidence: 99%